Ethnic and racial disparities in children's education: Comparative evidence from Ethiopia, India, Peru, and Viet Nam - Mohamed El Hedi Arouri; Adel Ben-Youssef; Cuong Nguyen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
We investigate whether there are racial and ethnic disparities in children's education in Ethiopia, India, Peru, and Viet Nam. We find that in all the four countries, and especially in Viet Nam, children from small ethnic groups have lower education attainment and cognitive ability. The gap in educational attainment and cognitive ability among ethnic children is larger than the gap in school enrolment, and the gap tends to be wider for older children. Using the Oaxaca-Blinder decomposition, we find that the main contribution to the gap in education between children from small ethnic groups and large ethnic groups in India, Peru, and Viet Nam is the difference in endowments (i.e. characteristics of children and their families) rather than in the coefficients of endowments. However, in Ethiopia, the difference in the coefficients contributes more than the difference in endowments to the gap in education. Child health, parental education, household expenditure, and an urban environment are important variables for explaining the gap in education between children from small and large ethnic groups.
Keywords: J13; J15; I21; 330; children's education; racial disparities; low-income countries; Ethiopia; India; Peru; Viet Nam